Handbook in social philosophy : with review materials in social philosophy and philosophy of education for the LET - Bauzon, Prisciliano T. (Metro Manila : National Book Store, 2002)
There are many books in Philosophy but there is a paucity of references in social philosophy especially one written for Filipino students. Social Philosophy, just like its mother discipline philosophy , is a universal field of study. The treatment presented in this book follows this main tenet.
Chapter 1. Introduction -- Chapter 2. The nature of philosophy as an autonomous branch of knowledge -- Chapter 3. Method of moral and social philosophical inquiry -- Chapter 4. Roles and condition of philosophy -- Chapter 5. Pre- philosophy and the era of world religions -- Chapter 6. Historical perspective of moral and social philosophy -- Chapter 7. The human person and human rights -- Chapter 8. Social philosophy and the natural positive law -- Chapter 9. Aristotle's social and political philosophy -- Chapter 10. Plato's social and political philosophy -- Chapter 11. Philosophy of moral and social values -- Chapter 12. Social philosophy in the ASEAN -- Chapter 13. Social values derived from the " LVEP: An educational programme" from selected countries -- Chapter 14. Social philosophies of selected philosophies -- Chapter 15. The nature of social man -- Chapter 16. Ibn Sina as a socio political philosopher: implications for the Philippine socio-political milieu -- Chapter 17. Supplementary chapter: review materials in social philosophy and philosophy of education for the licensure examination for teachers.
Includes bibliographical references.
Keywords: SOCIAL PHILOSOPHY